Glossary of Expressions in Biological Control - J. Howard Frank; Jennifer L. Gillett-Kaufman (EDIS)
IPM-143, a 12-page glossary by J. H. Frank and J. L. Gillett, attempts to prevent the spread of inaccuracy and confusion by providing definitions for a number of expressions used in biological control literature. Controversial terms are supplemented with discussion in footnotes. Includes references. Published by the UF Department of Entomology and Nematology, August 2006.